Integrating input-output modeling with multi-criteria analysis to assess options for sustainable economic transformation: the case of Uzbekistan - Bekchanov, Maksud; Bhaduri, Anik; Lenzen, M.; Lamers, John P.A. (2014)
Integrating economic efficiency and environmental sustainability indicators is essential for designing policies for a sustainable development. Given the growing pressure on water resources, efficient water use becomes an essential environmental criteria for formulating adjustment reforms. Despite the wide use of backward and forward linkages as well as direct and indirect resource (energy, water, etc.) uses based on environmentally extended input-output models for assessing the performance of economic sectors, the common practice of presenting different indicators separately obstructed a straightforward policy interpretation of results. To derive a composite indicator that allows to direct ranking of sectors, we combined therefore a direct and indirect water use intensities with backward and forward linkage indexes by using the multi-criteria analysis method-TOPSIS (Technique for order preference by similarity to ideal solution). The model was implemented to formulate sectoral transformation measures guided by sustainable growth objectives in Uzbekistan, Central Asia, which is a representative of an area with growing water scarcity. The results showed that the presently promoted crops under the state order system—cotton and wheat—and crop preferred by farmers— rice—are the least effective production options for reaching such a sustainable growth. It is argued therefore that unbiased support for all crops through adaption of the current state order system for cotton and wheat cultivation is needed to achieve a more diversified crop portfolio with an increased share of fruits and vegetables. A further development of agro-processing industries and livestock sector bears more potential for sustainable economic development than a further promotion of producing raw agricultural commodities. Investing in industrial sectors illustrated more potential than in agriculture related sectors when aiming at economic effectiveness and increased water use efficiency. It is concluded that, with a relevant sectoral transformation, Uzbekistan has high opportunities to cope with reduced water availability.